Differences in advanced magnetic resonance imaging in MOG-IgG and AQP4-IgG seropositive neuromyelitis optica spectrum disorders: a comparative study - Schmidt, Felix; Chien, Claudia; Kuchling, Joseph; Bellmann-Strobl, Judith; Ruprecht, Klemens; Siebert, Nadja; Asseyer, Susanna; Jarius, Sven; Brandt, Alexander U.; Scheel, Michael; Paul, Friedemann (Frontiers in neurology, 2020)
Aims: To explore differences in advanced brain magnetic resonance imaging (MRI) characteristics between myelin oligodendrocyte (MOG) immunoglobulin (IgG) and aquaporin-4 (AQP4) IgG seropositive (+) neuromyelitis optica spectrum disorders (NMOSD). Methods: 33 AQP4-IgG and 18 MOG-IgG seropositive NMOSD patients and 61 healthy control (HC) subjects were included. All 112 participants were scanned with the same standardized MRI-protocol on a 3-Tesla MRI-scanner. Brain volume and diffusion tensor imaging (DTI) parameters were assessed. Results: MOG-IgG+ patients showed reduced parallel diffusivity within white matter tracts compared to HC whereas AQP4-IgG+ showed no significant brain parenchymal damage in DTI analysis. AQP4-IgG+ patients showed reduced whole brain volumes and reduced volumes of several deep grey matter structures compared to HC whereas MOG-IgG+ patients did not show reduced brain or deep grey matter volumes compared to HC. Conclusions: Microstructural brain parenchymal damage in MOG-IgG+ patients was more pronounced than in AQP4-IgG+ patients, compared with HC, whereas normalized brain volume reduction was more severe in AQP4-IgG+ patients. Longitudinal imaging studies are warranted to further investigate this trend in NMOSD. Our results suggest that MOG-IgG+ and AQP4-IgG+ NMOSD patients differ in cerebral MRI characteristics. Advanced MRI analysis did not help to differentiate between MOG-IgG+ and AQP4-IgG+ patients in our study.